Implementation of link workers in primary care: Synopsis of findings from a realist evaluation - Stephanie Tierney; Geoff Wong; Debra Westlake; Amadea Turk; Steven Markham; Jordan Gorenberg; Joanne Reeve; Caroline Mitchell; Kerryn Husk; Sabi Redwood; Tony Meacock; Catherine Pope; et al. (Health and Social Care Delivery Research, 2025)
Background Social prescribing link workers formed part of the Additional Roles Reimbursement Scheme introduced into primary care in England from 2019. Link workers assist patients experiencing issues affecting their health and well-being that are ‘non-medical’ (e.g. lack of social connections, financial difficulties and housing problems). They give patients space to consider these non-medical issues and, when relevant, connect them to support, often within the voluntary–community–social–enterprise sector. We conducted an earlier realist review on the link worker role in primary care. We then carried out a realist evaluation, described in this report, to address the question: When implementing link workers in primary care to sustain outcomes – what works, for whom, why and in what circumstances? Aim To develop evidence-based recommendations to optimise the implementation of link workers in primary care and to enable patients to receive the best support possible. Design A realist evaluation, involving two work packages. Setting Data were collected around seven link workers in different parts of England. Methods For work package 1, researchers spent 3 weeks with each link worker – going to meetings with them, watching them interact with patients, with healthcare professionals and with voluntary–community–social–enterprise staff. During this time, researchers had a daily debrief with the link worker, inviting them to reflect on their working day, and they collected relevant documents (e.g. job descriptions and information on social prescribing given to patients). They also conducted interviews with 93 primary care/voluntary–community–social–enterprise staff and 61 patients. As part of this work package, data on patient contact with a general practitioner before and after being referred to a link worker were collected. Work package 2 consisted of follow-up interviews (9–12 months later) with patients; 41 were reinterviewed. In addition, link workers were reinterviewed. A realist logic of analysis was used to test (confirm, refute or refine) the programme theory we developed from our realist review. Analysis explored connections between contexts, mechanisms and outcomes to explain how, why and in what circumstances the implementation of link workers might be beneficial (or not) to patients and/or healthcare delivery. Results We produced three papers from the research – one on link workers ‘holding’ patients, one on the role of discretion in their job, and another exploring patient-focused data and readiness to engage in social prescribing. Data from these papers were considered in relation to Normalisation Process Theory – a framework for conceptualising the implementation of new interventions into practice (e.g. link workers into primary care). By doing so, we identified infrastructural factors required to help link workers to: (1) offer person-centred care; (2) develop patients’ self-confidence, sense of hope and social capital; (3) facilitate appropriate general practitioner use; (4) foster job satisfaction among those delivering social prescribing. Discussion Our research highlighted the importance of a supportive infrastructure (including supervision, training, leadership/management, clarity about the role, link workers’ ability to use existing skills and knowledge and having capacity to connect with providers in the voluntary–community–social–enterprise sector) in order to produce person-centred care, to nurture hope, self-confidence and social capital among patients, to ensure they receive the right support (medical or non-medical), and to promote link workers’ job satisfaction. Data showed how link workers can contribute to the offer of holistic care beyond a purely medical lens of health and illness. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number NIHR130247. Plain language summary Approximately, one in five people see their general practitioner with problems that are social (e.g. loneliness), environmental (e.g. housing) or economic (e.g. debt). These ‘non-medical’ issues can affect how someone feels (physically or mental health wise). Social prescribing is one way to help. It involves connecting people to ‘community assets’ (e.g. a local group to meet others and an organisation that provides advice on housing/finances). Link workers are employed to deliver social prescribing in primary care. They meet with a patient (usually more than once) to find out what is happening in this person’s life and what they want to change/address. Link workers can connect patients to relevant community support or services. Our research focused on how link workers are being used in primary care. We collected data around seven link workers based in different parts of England. We spent 3 weeks with each link worker. We watched these link workers meeting with patients, healthcare staff and voluntary–community sector representatives. We also conducted interviews with 93 professionals (working in primary care or the voluntary–community sector) and 61 patients. We reinterviewed 41 patients, 9–12 months later, along with 7 link workers and a link worker manager. Key ideas from our data included: (1) link workers are an ongoing source of support for patients, who are relied on to listen to their difficulties; (2) link workers need flexibility in how they work to best assist patients and to develop a good working relationship with healthcare colleagues and (3) patients trust link workers to support them. Our study shows important changes needed to support link workers. These include: (1) establishing a clear definition of the job; (2) providing adequate supervision and training and (3) ensuring link workers have time to focus on non-medical issues and to develop relationships with community providers. The study is registered as research registry in 2021 (www.researchregistry.com/browse-the-registry#home/registrationdetails/5fff2bec0e3589001b829a6b/).